Analisis Pesan Persuasif Kelompok Cyberprotest di Twitter - Aisyah, Vinisa Nurul (Jurnal Studi Komunikasi, 2020)
This study analysed persuasive messages by cyberprotest group on Twitter, especially in the case of Jaringan Masyarakat Peduli Pegunungan Kendeng (JMPPK) Rembang. Persuasive messages on Twitter were identified based on argument type, interaction type, and messages format. This study used elaboration likelihood model and quantitative content analysis method. The result of the study indicated that Twitter could be used as a persuasive communication space for protest groups. Central and peripheral route were facilitated by the features provided by Twitter.